Chronic cadmium exposure induces epithelial mesenchymal transition in prostate cancer cells through a TGF-β-independent, endoplasmic reticulum stress induced pathway. (15th December 2021) - Hu, Weirong; Xia, Mizhen; Zhang, Cheng; Song, Bingdong; Xia, Zhengmei; Guo, Chunyu; Cui, Yingying; Jiang, Weiying; Zhang, Shicheng; Xu, Dexiang; Fang, Jun
Graphical abstract: Highlights: Chronic Cd exposure induces EMT and malignant changes of prostate cancer cells. EMT is triggered via a TGF-β- independent pathway. ROS-mediated ER stress/ Smad3 pathway play essential role on Cd induced EMT. NAC could reverse malignant changes of prostate cancer cells evoked by Cd. Antioxidant or targeting ER stress may be a useful tool to control prostate cancer. Abstract: In this study, we aimed to elucidate the role of chronic cadmium (Cd) exposure in epithelial-mesenchymal transition (EMT) and thus malignant phenotypic changes of prostate cancer cells. Prostate cancer cells (PC-3 and DU145) were exposed to a non-toxic level (0.5 or 2 μM) of Cd for up to 3 months, which resulted in significantly promoted migration and invasion of the cells. These phenotypic changes were considered to be the consequence of enhanced EMT as evidenced by diminished expression of E-cadherin and increased vimentin expression. Regarding the mechanisms of Cd-induced EMT, we found Smad3 was activated but without upregulation of TGF-β. Alternatively, we found endoplasmic reticulum (ER) stress of prostate cancer cells was significantly evoked, which was parallel with the increased reactive oxygen species (ROS). Removal of ROS by N-acetylcysteine significantly reduced ER stress in prostate cancer cells, followed by the decrease of Smad3 phosphorylation and expression of nuclear Snail, resulting in the inhibition of EMT and malignant phenotypic changes of prostate cancer cells. These findings indicated a new TGF-β independent, ROS-mediated ER stress/Smad signaling pathway in chronic Cd exposure-induced EMT of prostate cancer cells, which could be a novel mechanism involved in cadmium-mediated cancer cells malignant transformation. Accordingly, ROS-induced ERs may become a novel preventive and therapeutic target for cancer.